COMPARATIVE STUDY OF WORD FORMATION IN ENGLISH AND UZBEK LANGUAGES (Modern education and development, 2025)
This article provides a comprehensive comparative study of word formation processes in the English and Uzbek languages, emphasizing both structural mechanisms and semantic implications. It systematically analyzes the ways in which new words are created in these two typologically different languages. English, as an analytic language, relies significantly on syntactic constructions and less on morphological change, whereas Uzbek, as an agglutinative language, extensively uses suffixation and morphological inflection to express grammatical and lexical meaning. The article delves into major word formation techniques such as affixation, compounding, conversion, blending, and clipping in English, and compares them with corresponding methods in Uzbek, including suffixation, compounding, reduplication, and derivational morphology. In addition to outlining the similarities and differences in morphological processes, the study discusses the linguistic, cultural, and functional factors that influence lexical productivity in both languages. This comparative analysis contributes to a deeper understanding of how language typology affects word formation and offers valuable perspectives for fields such as contrastive linguistics, translation studies, second language acquisition, and lexicography.